A small molecule inhibitor of leucine carboxyl methyltransferase-1 inhibits cancer cell survival - O. A. Arosarena; O. A. Arosarena; O. A. Arosarena; A. S. Saribas; E. P. Papadopoulos (Frontiers Media S.A., 2024)
Reversible phosphorylation is the basis for signal transduction in eukaryotic cells, and this is tightly controlled by the complex interplay of kinases and phosphatases. Many malignancies are characterized by dysregulation of the delicate protein phosphorylation balance. The targeting of protein phosphatases has been gaining attention as their role in cancer development and progression has been elucidated. The protein phosphatase-2A (PP2A) family of phosphatases are the primary cellular serine/threonine phosphatases. PP2A heterotrimers containing the B55α (PR55α) regulatory subunit have been associated with oncogenic signaling, and B55 subunits are found exclusively in forms of PP2A in which the carboxyl terminus of the catalytic subunit (PP2Ac) is methylated. Methylation of PP2Ac is primarily mediated by leucine carboxyl methyltransferase-1 (LCMT-1). Demethylation is controlled by an esterase, PP2A methylesterase (PME-1). We tested two potential LCMT-1 small molecule inhibitors and found that methyl 4-methyl-2-[(2-methylbenzoyl)amino]-5-[[(3-methylphenyl)amino]carbonyl]-3-thiophenecarboxylate (henceforth referred to as Compound 2) significantly inhibited PP2Ac methylation in vitro (p = 0.0024), and in the MDA-MB-231 breast carcinoma (p = 0.0431) and Rosi melanoma (p = 0.0335) cell lines. Compound 2 significantly reduced survival in HEK-293, HS-5, MDA-MB-231 and Rosi cells; and constrained clonogenic colony formation in MCF7, MDA-MB-231 and Rosi cells. The LCMT-1inhibitor induced G0/G1 cell cycle arrest in Rosi cells (p = 0.0193) and induced apoptosis in MDA-MB-231 cells (p < 0.0001). Increased phosphorylation of the receptor-interacting serine/threonine protein kinase-1 (RIPK1) was detected in MDA-MB-231 (p = 0.0273) and Rosi cells (p = 0.0179) in response to treatment with Compound 2. These data add to the body of evidence pointing to LCMT-1 as an oncogenic target.